(untitled) (Bangladesh Journal of Medical Education, 2019)
This descriptive type of cross sectional study was conducted in twelve medical colleges of Bangladesh to assess the views of teachers and students regarding the distribution of subjects in Phase II and Phase III of MBBS curriculum 2012. This study was conducted from July 2017 to Apr 2018 where views were collected from 91 teachers and 991 students. Study revealed that, 90.1% respondents mentioned for rearrangement of subjects and around 87.9% teachers and 90.3% students opined for addition of Pathology subjects in Phase II of MBBS course. Study also recommended that more extensive study is needed to get an unanimous opinion from the students and medical teachers regarding the subjects in Phase II and Phase III of MBBS course. Bangladesh Journal of Medical Education Vol.10(2) 2019: 19-22